The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2020
DOI: 10.1371/journal.pone.0240415
|View full text |Cite
|
Sign up to set email alerts
|

Ophidiomycosis, an emerging fungal disease of snakes: Targeted surveillance on military lands and detection in the western US and Puerto Rico

Abstract: Wildlife disease surveillance and pathogen detection are fundamental for conservation, population sustainability, and public health. Detection of pathogens in snakes is often overlooked despite their essential roles as both predators and prey within their communities. Ophidiomycosis (formerly referred to as Snake Fungal Disease, SFD), an emergent disease on the North American landscape caused by the fungus Ophidiomyces ophiodiicola , poses a threat to snake population health and stabilit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
23
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
3
2
2

Relationship

1
6

Authors

Journals

citations
Cited by 22 publications
(25 citation statements)
references
References 48 publications
0
23
0
Order By: Relevance
“…However, overall, prevalence was relatively low (8.7%) when compared to studies conducted in North America. of free-ranging snakes in the USA and Canada, with 9.8% observed mortality [30,33].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, overall, prevalence was relatively low (8.7%) when compared to studies conducted in North America. of free-ranging snakes in the USA and Canada, with 9.8% observed mortality [30,33].…”
Section: Discussionmentioning
confidence: 99%
“…However, overall, prevalence was relatively low (8.7%) when compared to studies conducted in North America. Samples collected from 31 states in the U.S. and Puerto Rico detected O. ophidiicola in 17.2% of wild snakes, and a meta-analysis of 33 studies reported overall O. ophidiicola infection in 18.5% of free-ranging snakes in the USA and Canada, with 9.8% observed mortality [30, 33].…”
Section: Discussionmentioning
confidence: 99%
“…O. ophidiicola is a generalist pathogen which is capable of infecting numerous snake species across the phylogeny (31, 33, 92). We acknowledge that the physiological response to this pathogen may vary among different host snake species, but we suspect that the biological mechanisms underlying host response (like immune activation, metabolism, etc.)…”
Section: Discussionmentioning
confidence: 99%
“…The emerging fungi pathogens threaten biodiversity more than any other group of microorganisms that can cause disease (Fisher et al, 2012). They are responsible for declines of many taxa, including fishes (Hatai, 2012;Rodger, 2016;Yanong, 2003), amphibians (Blaustein et al, 2018;Grogan et al, 2018;Hussain & Pandit, 2012;Rollins-Smith, 2017), and reptiles (Allender et al, 2020;Lorch et al, 2016;Schumacher, 2003). These declines are especially severe in amphibians, whose populations are declining worldwide (Blaustein et al, 2018;Collins, 2010).…”
Section: Emerging Fungal Pathogensmentioning
confidence: 99%
“…The ectotherms decline has multiple causes, emphasizing the increased prevalence and outbreaks of diseases caused by emerging pathogens, such as fungus and viruses, in amphibians (Blaustein et al, 2018;Chen & Robert, 2011;Grogan et al, 2018;Hussain & Pandit, 2012;Rollins-Smith, 2017), reptiles (Allender et al, 2020;Lorch et al, 2016;Marschang, 2019;Schumacher, 1997Schumacher, , 2003, and fishes (Hatai, 2012;Rodger, 2016;Yanong, 2003). This increase in the prevalence of pathogens and the resulting diseases, in turn, are associated with climate change and environmental contamination (Becker & Zamudio, 2011;Brem & Lips, 2008;Burrowes et al, 2004).…”
mentioning
confidence: 99%